Implementation of Augmented Reality Technologies in Artwork Creating Process - Sovhyra, Tetiana (Journal of History Culture and Art Research, 2020)
This article investigates the possibility of introducing and refining augmented reality (AR) technologies in the artwork creating process. In this context, the article examines cultural projects that AR technologies. The research methodology is a combination of several methods: analytical – for accounting for historical and fictional literature; theoretical and conceptual method – for analyzing the conceptual and terminological system of research and identifying the specifics of introducing the AR technology into cultural and artistic practice; comparative typological – for comparing AR and VR technologies, analyzing projects aimed at studying AI technologies and art interaction. The author has identified that in the process of creating augmented reality content, it is important to carefully link virtual models with the image of real space using markers. The author proves that the AR-compositions creation does not require significant financial resources and a large number of specialists. On the other hand, augmented reality technology provides significant advantages of viewing the necessary context: visualization, volumetric image, and interactive use of the necessary material. It has been established that virtual content can significantly change the content and ideological content of a work of art. Based on the marker image, a new artistic context is created and organized into an AR installation.